NPAHs and OPAHs in the atmosphere of two central European cities: Seasonality, urban-to-background gradients, cancer risks and gas-to-particle partitioning - Degrendele, Céline; Kanduč, Tjaša; Kocman, David; Lammel, Gerhard; Cambelová, Adriana; Dos Santos, Saul Garcia; Horvat, Milena; Kukučka, Petr; Holubová Šmejkalová, Adéla; Mikeš, Ondřej; Nuñez-Corcuera, Beatriz; Přibylová, Petra; et al. (The Science of the total environment, 2021)
Derivatives of polycyclic aromatic hydrocarbons (PAHs) such as nitrated- and oxygenated-PAHs (NPAHs and OPAHs) could be even more toxic and harmful for the environment and humans than PAHs. We assessed the spatial and seasonal variations of NPAHs and OPAHs atmospheric levels, their cancer risks and their gas-to-particle partitioning. To this end, about 250 samples of fine particulate matter (PM2.5) and 50 gaseous samples were collected in 2017 in central Europe in the cities of Brno and Ljubljana (two traffic and two urban background sites) as well as one rural site. The average particulate concentrations were ranging from below limit of quantification to 593 pg m-3 for Σ9NPAHs and from 1.64 to 4330 pg m-3 for Σ11OPAHs, with significantly higher concentrations in winter compared to summer. In winter, the particulate levels of NPAHs and OPAHs were higher at the traffic site compared to the urban background site in Brno while the opposite was found in Ljubljana. NPAHs and OPAHs particulate levels were influenced by the meteorological parameters and co-varied with several air pollutants. The significance of secondary formation on the occurrence of some NPAHs and OPAHs is indicated. In winter, 27-47% of samples collected at all sites were above the acceptable lifetime carcinogenic risk. The gas-particle partitioning of NPAHs and OPAHs was influenced by their physico-chemical properties, the season and the site-specific aerosol composition. Three NPAHs and five OPAHs had higher particulate mass fractions at the traffic site, suggesting they could be primarily emitted as particles from vehicle traffic and subsequently partitioning to the gas phase along air transport. This study underlines the importance of inclusion of the gas phase in addition to the particulate phase when assessing the atmospheric fate of polycyclic aromatic compounds and also when assessing the related health risk.
Keywords: pevné částice; Fine particles; Cities; Seasons; monitorování životního prostředí; Neoplasms; velkoměsta; nádory; Spatial variations; lidé; Particulate Matter; roční období; Polycyclic aromatic hydrocarbons; Air Pollutants; polycyklické aromatické uhlovodíky; Polycyclic Aromatic Hydrocarbons; Atmosphere; Environmental Monitoring; látky znečišťující vzduch; Cancer risk; Humans